A cross sectional study of dietary patterns and the association of perceived stress on body mass index among undergraduate medical students including compulsory residential rotatory interns - Nimmala, Supritha; Bhattacharya, Adhiraj; Ramraj, Balaji (International Journal Of Community Medicine And Public Health, 2018)
Background: Medical education proves to be a tough and stressful environment during which these young physicians-in-training gain large amounts of knowledge and skills. Previous studies regarding dietary habits, body mass index (BMI) and perceived stress failed to include Compulsory Residential Rotatory Interns (CRRI). This study encompassing medical undergraduate students of all years including CRRIs aims to identify dietary patterns and significant associations between dietary habits, Perceived Stress and BMI. Methods: Cross-sectional study conducted with sample size of 150 consisting of undergraduate medical students varying from the first year to CRRI at SRM Medical College, Hospital and Research Centre, Tamil Nadu. Dietary habits noted with an information schedule. BMI calculated using Quetelet’s Index. Cohen’s PSS-10 questionnaire provided to quantify Perceived Stress. Associations tested using Chi-square test and Correlation. Results: Prevalence of obesity -7% and overweight -26.7% with males having higher mean BMI. Majority at 52% perceived ‘moderate’ stress with males having higher mean PSS score. Awareness of balanced diet was 94.7% with 32% practicing balanced diet. Diet frequency was regular in 62% and 49.3% was skipping meals. 92.7% consumed junk food often and 13.3% partook in binge eating. 8% participated in crash diets and significant association found between this dietary factor and BMI. Significant correlation and positive linear relationship found between Perceived Stress and BMI. Conclusion: Higher levels of perceived stress among students including CRRIs lead to overall higher values of BMI indicates the need for stricter healthier dietary habits and psychological health services to relieve stress.